Le bilan sociétal : un outil de management pour renforcer l’ancrage territorial et la responsabilité sociale des coopératives agricoles - Yves Cariou; Sandrine Fournie; Fredéric Wallet (Développement Durable et Territoires)
In a context of deep changes in rural areas, and increasing questioning on the social responsibility of companies, agricultural co-operatives – because of their legal statute – can appear as major actors for territories sustainable development. However, the diversity of co-operative’s strategies underlines weaknesses of this statute to fulfil this mission, and the need for associating new tools to deepen the co-operative principles and take into account environmental concerns. For this reason, social assessment seems to be a relevant answer to establish a diagnosis of the co-operatives, integrating internal democracy, people promotion, solidarity, mutualism, territorial implication and respect of environment. After having pointed out the terms of this debate and presented the reasons why social balance sheet constitutes an innovation in management, we show the impact of its setting through the example of an agricultural cooperative the North-East of Lot County.